2018
DOI: 10.1037/cou0000300
|View full text |Cite
|
Sign up to set email alerts
|

Client feedback in China: A randomized clinical trial in a college counseling center.

Abstract: Although client feedback has been demonstrated to improve psychotherapy outcomes in over a dozen randomized clinical trials, no studies to date have investigated the feedback effect outside of the United States or Europe. This study examined the impact of a client feedback intervention, the Partners for Change Outcome Management System, in a college counseling center in Wuhan, China ( = 186). Using a randomized design within routine care, treatment as usual (TAU; = 85) was compared with a feedback condition ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Conclusion. Among other preliminary client outcome research efforts around the world (She et al 2018), this study supports the connection between postgraduate education conducted by the U.S. Counseling educational standards in Ukrainian environment and improved client outcomes. It also stands within the greater body of work examining the industry wide trend of utilizing outcome evaluation as a routine part of effective therapeutic services (Bringhurst, Watson, Miller, & Duncan, 2006).…”
Section: Interpretation Of Resultssupporting
confidence: 76%
“…Conclusion. Among other preliminary client outcome research efforts around the world (She et al 2018), this study supports the connection between postgraduate education conducted by the U.S. Counseling educational standards in Ukrainian environment and improved client outcomes. It also stands within the greater body of work examining the industry wide trend of utilizing outcome evaluation as a routine part of effective therapeutic services (Bringhurst, Watson, Miller, & Duncan, 2006).…”
Section: Interpretation Of Resultssupporting
confidence: 76%
“…Similarly, of the RCTs that included both the outcome and alliance components of PCOMS and an adequate dose of treatment (at least four sessions), all three studies that did not find an effect for PCOMS had significant adherence issues and/or therapists who perceived the feedback as not useful (Davidsen et al, 2017;Janse et al, 2017;van Oenen et al, 2016). PCOMS trials that include adherence checks and reinforcements of PCOMS use via supervision, graph checking, and data review have found a significant feedback effect (e.g., She et al, 2018).…”
Section: Discussion Feasibilitymentioning
confidence: 99%
“…Potentially, the CIP-Short can also be used to track the progress of career interventions. Research has shown that feedback from brief outcome measures can improve treatment efficacy, particularly for difficult cases (Anker, Duncan, & Sparks, 2009; She et al, 2018). Given its sound efficiency and psychometric properties, the CIP-Short has the potential to serve as a progress tracker/marker for career interventions.…”
Section: Discussionmentioning
confidence: 99%